Correlation between mitral annular plane systolic excursion (MAPSE) at different degrees of ejection fraction in patients with diabetes mellitus - Muhammad Rido; Khalid Saleh; A. Makbul Aman; Syakib Bakri; Haerani Rasyid; Andi Alfian Zainuddin (Romanian Medical Journal)
Background and aim. Diabetic cardiomyopathy is characterized by myocardial structure and function abnormality in the absence of other cardiovascular risk factors. Early detection of cardiac dysfunction is crucial for timely intervention and improved patient outcomes. The purpose of this study is to determine how mitral annular plane systolic excursion (MAPSE) is a sensitive marker of early cardiac dysfunction in patients with diabetes mellitus by examining the relationship between MAPSE values and different levels of ejection fraction. Methods and material. An analytical cross-sectional study was carried out at Dr. Wahidin Sudirohusodo Hospital in Indonesia's Integrated Heart Center. The sample included 79 patients with ages from 18 to 65 years old and a type 2 diabetes diagnosis. Data collected included age, gender, ejection fraction, and MAPSE. Statistical methods included descriptive analysis and Spearman correlation tests. Results. The study population was predominantly male (71%), with a mean age of 55.5 years for those without EF impairment and 59.5 years for those with impairment. The average impaired EF was 37.69%. MAPSE examination in septal, lateral, and average segments showed significant differences. There is a strong positive association between MAPSE and EF in all study samples. In patients with preserved EF (average EF 58%), MAPSE was 14.4 mm, and in those with reduced EF (average EF 29%), MAPSE was 6.31mm, with significant positive correlations. No significant results were observed in subjects with mid-range EF. Conclusions. This research revealed that mitral annular plane systolic excursion (MAPSE) is significantly associated with ejection fraction (EF) in individuals with diabetes mellitus (DM), mainly when EF is either well-maintained or diminished.